bio filler, breathable conglomerate, thermo physical modeling, bioresearches, fractions, shavings, fibers, gypsum, dry building mixtures, adhesion, cohesion, durability (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Development and application of dry plaster mixes is a relatively new direction in the technology of finishing works. This article presents the main results on the use of finely ground elements of wood and other vegetation included in the composition of gypsum plaster mixes. The main physical and mechanical properties and characteristic technological features of the proposed composition have been studied.